Active listing and more consultations in primary care are associated with shorter mean hospitalisation and interacting with psychiatric disorders when adjusting for multimorbidity, age and sex. (3rd July 2018) - Ranstad, Karin; Midlöv, Patrik; Halling, Anders
Abstract: Objective: Patient-provider relationships with primary care and need for hospitalisations are related within the complex networks comprising healthcare. Our objective was to analyse mean days hospitalised, using registration status (active or passive listing) with a provider and number of consultations as proxies of patient-provider relationships with primary care, adjusting for morbidity burden, age and sex while analysing the contribution of psychiatric disorders. The Johns Hopkins Adjusted Clinical Groups Case-Mix System was used to classify morbidity burden into Resource Utilization Band (RUB) 0-5. Design: Cross-sectional population study using zero-inflated negative binomial regression. Setting and subjects: All population in the Swedish County of Blekinge ( N  = 151 731) in 2007. Main outcome measure: Mean days hospitalised. Results: Actively listed were in mean hospitalised for 0.86 (95%CI 0.81–0.92) and passively listed for 1.23 (95%CI 1.09–1.37) days. For 0–1 consultation mean days hospitalised was 1.16 (95%CI 1.08–1.23) and for 4–5 consultations 0.68 (95%CI 0.62–0.75) days. At RUB3, actively listed were in mean hospitalised for 3.45 (95%CI 2.84–4.07) days if diagnosed with any psychiatric disorder and 1.64 (95%CI 1.50–1.77) days if not. Passively listed at RUB3 were in mean hospitalised for 5.17 (95%CI 4.36–5.98) days if diagnosed with any psychiatric disorder and 2.41 (95%CI 2.22–2.60) days if not. Conclusions: Active listing and more consultations were associated with a decrease in mean days hospitalised, especially for patients with psychiatric diagnoses. Implications: Promoting good relationships with primary care could be an opportunity to decrease mean days hospitalised, especially for patients with more complex diagnostic patterns. Key Points: Primary care performance, patient-provider relationships and need for hospitalisation are related within the complex networks comprising healthcare systems. Good patient-provider relationships, i.e. more consultations and active listing, with primary care are associated with decreasing mean days hospitalised. The impact of patient-provider relationships in primary care on mean days hospitalised increased when psychiatric disorders added to patient complexity.